Emerging roles of astrocytes in hippocampal circuitry and behavior - Squires, Ada; Park, Joongkyu (Frontiers in Cellular Neuroscience, 2025)
The discovery of neuronal activity-dependent calcium transients in astrocytes has driven the conceptualization of these cells as computational units in the nervous system. Tripartite synapses, consisting of pre- and postsynaptic terminals along with an adjacent astrocyte, enable astrocytes to communicate with and shape the activity of local synapses. In the hippocampus, astrocytes encode and modulate information through a variety of mechanisms, including tuning the gating of single synapses in their domains, coordinating oscillatory activity across neuronal circuits through astrocytic networks, and providing a foundation for long-term memory formation through intracellular signaling and metabolic coupling. The bidirectional and complementary activities of astrocytes and neurons can be situated in a framework that positions astrocytes as integrators and modulators of neuronal activity, both locally and globally. In this review, we focus on hippocampal astrocytes and discuss recent progress toward understanding astrocytic function in concert with neurons to mediate circuit function and, ultimately, behavior.